Morning Serum Cortisol and ACTH Levels in Cushing’s Syndrome: Correlation with Neuropsychiatric Manifestations - Junaid Rasool, Muhammad Waqas, Mahboob Qadir, Shakil Asif, Tashfeen Ikram, Beenish Sohail, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Cushing’s syndrome, characterized by chronic hypercortisolemia, produces multisystemcomplications extending far beyond metabolic disruption. Among these, neuropsychiatric manifestations—ranging from depression